The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/slct.201702259
|View full text |Cite
|
Sign up to set email alerts
|

Superbase‐Added Choline Chloride‐Based Deep Eutectic Solvents for CO2 Capture and Sequestration

Abstract: Deep eutectic solvents (DESs) have emerged as inexpensive and environmentally‐benign liquid media for potential usage in chemical sciences. CO2 capture and sequestration by various substances is an active area of research in green chemistry. CO2 capture ability of DES‐based systems composed of salt choline chloride mixed with hydrogen bond donors urea (named reline), ethylene glycol (named ethaline), and monoethanolamine (named MEACC), are assessed in the absence and presence of three superbases: 1,5‐diazabicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…DESs have been investigated for CO 2 capture, as they can absorb CO 2 through the entropic voids within the liquid, similar to nonreactive ILs. , A DES is a mixture for which the melting point is significantly lower than either of the parent compounds: a hydrogen bond acceptor (HBA), usually a halide salt, and a hydrogen bond donor (HBD), such as EG. Recent studies showed that DESs and DES-like mixtures with superbase additives, superbase HBAs, or superbases as the tertiary component have CO 2 capacities ranging from 3.6 to 17.34 wt % at 1 bar of CO 2 with typical absorption temperatures of 45–60 °C. The highest gravimetric CO 2 capacity at 33.7 wt % is reported for a mixture of monoethanolammonium chloride, [MEA.Cl], and ethlyenediamine at 1 bar of CO 2 and 30 °C .…”
Section: Introductionmentioning
confidence: 99%
“…DESs have been investigated for CO 2 capture, as they can absorb CO 2 through the entropic voids within the liquid, similar to nonreactive ILs. , A DES is a mixture for which the melting point is significantly lower than either of the parent compounds: a hydrogen bond acceptor (HBA), usually a halide salt, and a hydrogen bond donor (HBD), such as EG. Recent studies showed that DESs and DES-like mixtures with superbase additives, superbase HBAs, or superbases as the tertiary component have CO 2 capacities ranging from 3.6 to 17.34 wt % at 1 bar of CO 2 with typical absorption temperatures of 45–60 °C. The highest gravimetric CO 2 capacity at 33.7 wt % is reported for a mixture of monoethanolammonium chloride, [MEA.Cl], and ethlyenediamine at 1 bar of CO 2 and 30 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur dioxide (SO 2 ), another greenhouse gas, is one of the main constituents responsible for acid deposition, which has adverse effects on materials, natural resources, and human health . In the past, in order to mitigate the emission of CO 2 and SO 2 gases, researchers have put forth enormous effort for the development of various technologies to capture them. The most efficient and commonly used industrial technique to capture CO 2 is amine-based postcombustion CO 2 capture. , However, this technique has several drawbacks like amine degradation, equipment corrosion, and environmental issues. Similarly, to mitigate SO 2 emission, most industrial processes use the wet limestone flue gas desulfurization technique. , However, this method is irreversible and leads to unwanted byproducts. , Therefore, the search for a superior method to overcome the drawbacks of conventional methods led the researchers toward the use of novel materials such ionic liquids (ILs). Owing to their unique properties, ILs exhibited significant gas separation propensity. , Although gas absorption by ILs is a reversible process , with no side products, ILs are barely used in industries for gas capturing on a large scale because of their high production cost and low absorption capacity. , Recently, deep eutectic solvents (DESs) have emerged as alternative media for capturing gases because of their biodegradable nature, ease of preparation, and lower cost of the starting materials. DESs are commonly referred to as IL analogs because they share similar properties such as tunable character, high thermal stability, and low vapor pressure along with some new improved properties like biodegradability and low toxicity. ...…”
Section: Introductionmentioning
confidence: 99%
“…Because of their numerous favorable properties, the role of DESs in the field of gas capture was explored through a series of experimental works. Li et al highlighted the effect of temperature and pressure on the solubility of CO 2 at different compositions of choline–chloride ([Ch]­[Cl]) and urea . The authors showed that the solubility of CO 2 increased with increasing CO 2 pressure and decreased with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of DESs have been prepared as CO 2 absorbents so far. Among them, amine-based DESs [ 12 , 13 , 14 , 15 , 16 ], anion-functionalized DESs [ 17 , 18 ], and superbase-based DESs [ 19 , 20 , 21 , 22 ] showed attractive CO 2 capacities through the reaction between CO 2 and active sites in the components at ambient pressure, suggesting that adjusting the structures of the components in the DESs can be an effective strategy to meet the particular demands. Moreover, the interactions between CO 2 and the functionalized DESs were also reported in the literatures.…”
Section: Introductionmentioning
confidence: 99%